ANTICOAGULANT THERAPY IN EVERYDAY CLINICAL PRACTICE: DATA OF THE RETROSPECTIVE CROSS-SECTIONAL STUDY - V. A. Sulimov; D. A. Napalkov; A. A. Sokolova; A. V. Jilenko; O. S. Anikina (Рациональная фармакотерапия в кардиологии)
Aim. To study the structure and incidence of the in-hospital anticoagulants prescription in patients at high risk of thromboembolic events (TEE) and to evaluate clinical characteristics of anticoagulated patients (by the example of the University Clinical Hospital (UCH) №1 of I.M. Sechenov First Moscow State Medical University (FMSMU).Material and methods. The cross-sectional retrospective study held in UCH №1 of the FMSMU, enrolled 677 patients with atrial fibrillation (AF) for whom the prevention of TEE was indicated.Results. Of 677 analyzed cases (women 70%, men 30%) only 61% of the patients received appropriate anticoagulant therapy. Warfarin was prescribed in 73% of the cases, of them unsatisfactory international normalized ratio (INR) control (time in therapeutic range less than 60%) was revealed in 79%. 8.45% of the vitamin K antagonist treated patients developed hemorrhagic complications. 16% of the patients received novel oral anticoagulants (dabigatran – 14%, rivaroxaban – 2%). Bleeding was fixed in 4.2% of the dabigatran treated patients and in 14.3% - in case of rivaroxaban therapy.Conclusion. More than a third of non-valvular AF patients receive inadequate antithrombotic therapy in routine clinical practice. 75% of the anticoagulated patients are prescribed the vitamin K antagonists (typically warfarin) as a traditional anticoagulant. At that, only in 21.7% of the patients receiving vitamin K antagonists, this therapy may be considered adequate. Low incidence rate of the novel oral anticoagulants prescription despite the advantages of such treatment also calls attention.